Age at First Gestation in Beef Heifers Affects Fetal and Postnatal Growth, Glucose Metabolism and IGF1 Concentration - Lopez Valiente, Sebastian (2021)
This study aimed to determine the effects of age at first gestation on offspring growth performance, glucose metabolism, and IGF1 concentration. Heifers impregnated by AI from a single bull at 15 months of age (15 M, n = 20), or 27 months of age (27 M, n = 20), and multiparous cows (adult, n = 20) were used. Dams from all groups were managed in a single group during gestation and lactation. Gestational length was longer in the 15 M and 27 M than in adult dams (p = 0.009). Bodyweight at birth, at weaning and ADG during lactation were higher in calves from adult dams than in those from 27 M dams, and higher in calves from the latter than in 15 M calves (p < 0.001). Calves from 15 M dams had an increased head circumference/BW ratio compared to calves from 27 M dams, while calves from this latter group had an increased ratio compared to calves from adults (p = 0.005). Body mass index was greater in calves from adults than in those from 15 M and 27 M dams (p = 0.002). Milk production from 15 M and 27 M dams was similar but lower than that from adults (p = 0.03). Calves born from adult dams had greater blood glucose concentrations than those from 15 M and 27 M dams (p < 0.05). Serum IGF1 concentrations were higher in calves from adults than in calves from 15 M and 27 M dams (p = 0.01). This study showed that age at first gestation affects offspring postnatal growth performance, glucose metabolism and IGF1 concentration.